Water irrigation system using sms notification - Muhammad Shafiq, Mohamad Arif (2016)
This thesis is discussing the development of a Water Irrigation System using SMS Notification for an organization or user that organize their plant .Water Irrigation System is a system that use real device that will control to maintain water in the soil. The objective of the system was design a constant water irrigation monitoring system and develop SMS notification to user. The programmed plant watering system is made was to make the nursery worker or user works effectively. There were different sort of utilizing programmed watering systems like utilizing sprinkler systems, tube, nozzles and other. This anticipate utilizes Arduino board, which comprises of R3 Microcontroller. It is modified in a manner that it will sense the dampness level of the plants and supply the water if required. ADDIE model were the best methodology I used for this system. I have built up a prototype, which makes a plant more independent and watering itself from a medium water tank included the prototype reports status and flow conditions. Furthermore, it reminds the client to refill the water tank. The system computerization is intended to be assistive to the client. I trust that through this model, individuals will appreciate having plants without the difficulties identified with truant or distraction.